Correlation between Persistent Serum Lactate Elevation and Brain Magnetic Resonance Imaging Abnormalities in Children with Status Epilepticus - Prastiya Indra Gunawan; Riza Noviandi; Sunny Mariana Samosir (Korean Child Neurology Society, 2024)
Purpose This study was conducted to evaluate the correlation between persistent serum lactate elevation and brain magnetic resonance imaging (MRI) in children with status epilepticus (SE). Methods In this prospective analytical study, serum lactate levels were measured 24 hours after episodes of SE, and brain MRI was performed within 7 to 14 days after SE termination. MRI abnormalities were classified as acute encephalopathy (AE) grade I to III. The Kruskal-Wallis test was utilized for statistical analysis. Results The study included 42 participants with SE, of whom 85.70% were boys, with a mean age of 4.94 years. Viral encephalitis was the most common diagnosis, accounting for 47.60% of cases. Elevated serum lactate levels were detected in 71.40% of patients, and approximately 47.60% exhibited abnormal MRI findings consistent with AE grade I. The median serum lactate levels for AE grades I, II, and III were 1.50, 3.10, and 0.78 mmol/L, respectively. Two patients died, and 66.70% experienced neurologic sequelae. A significant correlation (P=0.021) was observed between persistent serum lactate elevation and abnormal brain MRI findings. Conclusion In children with SE, AE grade I was the most common neuroimaging pattern observed, and persistently elevated serum lactate level was correlated with abnormal brain MRI findings.